Nondestructive characterization of the polycarbonate - octadecylamine interface by surface enhanced Raman spectroscopy. (February 2019) - Zimmerer, C.; Matulaitiene, I.; Niaura, G.; Reuter, U.; Janke, A.; Boldt, R.; Sablinskas, V.; Steiner, G.
Abstract: Polymer composite materials are used increasingly in material and engineering science. They provide outstanding mechanical and optical properties. The linkage between the polymer materials is crucial for achieving the desired properties. Understanding the linkage and structure of the polymer-polymer interface layer is a key for utilization polymer composite materials as well as for their fabrication. When analyzing the thin polymer-polymer interface it is important to achieve clear identification of molecular linker structures. One reliable analytical technique allowing this is surface enhanced Raman scattering (SERS) spectroscopy. This study aims at the in-situ evaluation of SERS spectra recorded from the Polycarbonate (PC) –Octadecylamine (ODA) interface to identify the formation of urethane bonds. The detailed analysis of SERS spectra taken before and after the chemical linkage reaction reveals the formation of urethane structures, indicating a chemical bond between PC and ODA. The spectral pattern of urethane groups was identified and evaluated by a reference Raman spectrum. Graphical abstract: Image 1 Highlights: Nondestructive in-situ characterization of polymer interphase by SERS. Silver nanoparticles located at the polymer interface. Evaluation of molecular interphase structure between Polycarbonate-Octadecylamine. Formation of an initial urethane linkage.